Influence of CoO Nanoparticles on Properties of Barium Zirconium Titanate Ceramics - Jarupoom P. (2017)
© 2017, The Minerals, Metals & Materials Society. Composites of Ba(Zr 0.07 Ti 0.93 )O 3 ceramic and CoO nanoparticles (at 1.0 vol.% to 3.0 vol.%) have been fabricated to investigate the effects of the CoO nanoparticles on the properties of the composites. X-ray diffraction data revealed that the modified samples contained Ba(Zr 0.07 Ti 0.93 )O 3 and CoO phases. Addition of CoO nanoparticles improved the magnetic behavior and resulted in slight changes in ferroelectric properties. The composites showed a magnetoelectric effect in which the negative value of the magnetocapacitance increased with increasing CoO concentration. Examination of the dielectric spectra showed that the two phase-transition temperatures as observed for unmodified Ba(Zr 0.07 Ti 0.93 )O 3 merged into a single phase-transition temperature for the composite samples. The composite samples also showed broad relative permittivity versus temperature (ε r –T) curves with frequency dispersion. This dielectric behavior can be explained in terms of the Maxwell–Wagner mechanism. In addition, the Vickers hardness (H v ) value of the samples increased with increasing CoO content.